CHALLENGES AND OPPORTUNITIES IN IMPLEMENTING SUSTAINABLE HRM IN DEVELOPING COUNTRIES - Ashari Ariandi Nasution; Akhmad Soleh Rowandi Siregar; Zulmi Syahputra; Hairul Hanafi Purba; Rizki Adha; Malik Syahputra Purba; Rakesh Sitepu; Anggia Sari Lubis (CV. Radja Publika, 2025)
Sustainable Human Resource Management (Sustainable HRM) has gained increasing attention as organizations seek to balance economic performance, social responsibility, and environmental sustainability. In developing countries, the implementation of Sustainable HRM presents unique challenges and opportunities due to economic constraints, institutional limitations, cultural diversity, and varying levels of technological readiness. This paper aims to examine the key challenges faced by organizations in adopting Sustainable HRM practices in developing countries, including limited resources, lack of awareness, weak regulatory frameworks, and resistance to change. At the same time, it explores emerging opportunities such as digital transformation, growing stakeholder pressure for sustainability, and the potential of human capital development to support long-term organizational and societal goals. By reviewing relevant literature and contextual factors, this study highlights the strategic role of HRM in promoting sustainable development. The findings are expected to contribute to a deeper understanding of how organizations in developing countries can leverage Sustainable HRM as a driver of competitive advantage and sustainable growth.